Armed politics and the study of intrastate conflict. (July 2017) - Staniland, Paul
Though the two are often conflated, violence is not identical to conflict. This article makes the case for studying state-armed group interactions across space, time, and levels of violence as part of an 'armed politics' approach to conflict. It conceptualizes and measures armed orders of alliance, limited cooperation, and military hostilities, and the termination of these orders in collapse or incorporation. The article applies this framework to four contexts in South Asia. It measures armed orders across five groups and six decades in Nagaland in India, and then offers a briefer overview of state-group armed orders in Karachi in Pakistan, Mizoram in India, and Wa areas of northern Burma/Myanmar. Examining armed politics improves our understanding of ceasefires and peace deals, rebel governance, and group emergence and collapse, among other important topics. This approach complements existing data on civil conflict while identifying a new empirical research agenda and policy implications.